Respuesta :

ak78
m - x = y^2
y=√(m - x)

Answer:

[tex]y=\sqrt{m-x}[/tex]

Step-by-step explanation:

We have been given an equation [tex]m=x+y^2[/tex]

We need to rearrange the formula for y that means value of y in terms of other present variables in the equation we will get

[tex]y^2=m-x[/tex]  shifting x on left hand side of the given equation

After simplification means shifting square of the term to the other side of the equation we will get [tex]y=\sqrt{m-x}[/tex]

Therefore, [tex]y=\sqrt{m-x}[/tex]